Mengeksplorasi Perubahan Sifat Kerja Dan Kinerja ASN Pemerintah Daerah Jawa Timur Pasca Covid-19 - Mudrifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Local governments should maximize employee to produce improved outcomes and efficiency. Performance is related to the result and how the job process is carried out since it is this process that determines a person's level of achievement at work. What needs to be understood is how the Civil Servants' efficiency can be optimized, and leaders must pay attention to enhancing their performance. This study aims to examine the effect the of change nature of work on the performance of Indonesian local government civil servants in the post-Covid-19 period. The result shows that to build good collaboration, it is necessary to understand between employees so that no miscommunication and leaders can manage subordinates well with attitude deep concern for their employee. It also requires high responsiveness, responsibility, and transparency in decision making. Besides that, it is necessary to understand the importance of cooperation to providing socialization to all employees.